Factors influencing social-learning experience in nearby pocket parks on campus ground - Salih, Sarah; Ismail, Sumarni; Ismail, Nor Atiah; Ujang, Norsidah; Asif, Nayeem (2022)
Nearby pockets on campus grounds have become necessary learning sustainable settings to improve the academic experience by promoting outdoor social and learning activities. However, many universities still focus mainly on formal indoor learning and lack outdoor education that meets modern academic outcomes. Therefore, the current study aimed to identify the factors affecting students' social-learning experience in nearby pocket parks on campus ground, focusing on the tropical regions. The current study employed a questionnaire survey conducted in three Malaysian universities to collect data from 408 participants. The results showed various types of influencing factors that affect the social-learning experience in nearby pockets on campus ground, including landscape elements and activities, environmental factors, and access to these spaces. The results also indicated that students' demographics, including gender, education status, and university, influenced the outdoor social-learning experience. The current study contributed information to the development of on-campus sustainable settings for integrating nearby pockets in social interaction and learning activities in order to improve the academic social-learning experience.